Electrochemical behaviour of 2,8-dihydroxyadenine at a glassy carbon electrode - Diculescu, Victor C. (2007)
The electrochemical behaviour of 2,8-dihydroxyadenine (2,8-DHA)- the main adenine oxidation product- has been investigated over a wide pH range at a glassy carbon electrode (GCE) using cyclic, differential pulse and square wave voltammetry.